Affecting Organizational Resilience through High-performance Work Systems (HPWS):: A Moderated Mediation Model - Bin Mustakim, Afif (Jahangirnagar University Journal of Management Research, 2026)
Organizational resilience refers to the organizational ability to plan and implement sustainable measures to ensure long-term survival and growth after anticipating forthcoming challenges from multidimensional environmental sources. Such anticipatory and practical responses most often depend on the creativity of the employees. When an organization deploys HPWS, employee self-efficacy rises and may result in more creative solutions. Moreover, it is widely accepted that employees’ capacity to transfer knowledge into actions boosts their self-efficacy and creativity. This research has formed a moderated mediation framework based on the attitude-behavior-context (ABC) model to examine the relationship between HPWS and organizational resilience, where employee self-efficacy mediates the link between HPWS and employee creativity, and knowledge transfer capacity moderates the relationship between HPWS and employee self-efficacy. Furthermore, the study tested whether employee creativity has a subsequent impact on organizational resilience. Data are collected using a structured questionnaire from front desk managers working in courier companies engaged in parcel delivery service. The snowball sampling method was applied to gather 216 valid responses after distributing 400 questionnaires. The appropriateness of the SEM model is confirmed by confirmatory factor analysis and testing the measurement model using the SmartPLS 4.1.02 version. The study finds that HPWS significantly relates to employee creativity and employee self-efficacy, whereas employee self-efficacy has no significant mediating role in the relationship between HPWS and employee creativity. Besides, employee knowledge transfer capacity has also failed to moderate the relationship between HPWS and employee self-efficacy. Finally, the study has found a significant relationship between employee creativity and organizational resilience. The findings will attract future researchers to investigate moderating and mediating factors in the stated relationships. Besides, corporations will be more careful in administering HPWS to increase employee self-efficacy, employee creativity, and maintain resilient behavior.